Power analysis attack of HMAC based on SM3 - Zhi-bo DU; Zhen WU; Min WANG; Jin-tao RAO (Tongxin xuebao)
The current power analysis attack of HMAC based on SM3 applies only to the object,on which there is the Hamming weight and Hamming distance information leakage at the same time.there is only a single information leakage mode on the attack object,then the attack methods don't work.To solve the limitations of the current attack methods,a novel method of the power analysis attack of HMAC based on SM3 was proposed.The different attack object and their related va-riables were selected in each power analysis attack.The attacks were implemented according to the Hamming distance mod-el or Hamming weight model of the intermediate variables.After several power analysis attacked on the first four rounds of SM3,the equations that consists of the results proposed of all the power analysis attacks were obtained.The ultimate attack object is derived by getting the solution of the equations.The experimental results show that the oposed attack method was effective.The method can be used universally because its being available for both the situation of co-exist of hamming weight with Hamming distance,and that of either the Hamming weight or choosing the Hamming distance model existence.